Solvent capacity of different substances on gutta-percha and resilon - Tanomaru-Filho, Mário [UNESP]; Orlando, Tais d'Azeredo [UNESP]; Bortoluzzi, Eduardo Antunes; da Silva, Guilherme Ferreira [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP] (FapUNIFESP (SciELO), 2010)
The aim of this study was to evaluate the effectiveness of 3 solvents (eucalyptol, orange oil, and xylol) on 2 types of gutta-percha (conventional and thermoplastic) and Resilon. Specimens (10 mm diameter × 1 mm thick; n=7 per condition) were prepared and maintained at 37°C for 48 h. Each specimen was weighed on a precision scale every 24 h until its mass was stable, at which time the initial mass was determined. Specimens (n=7) were then immersed in the solvent solutions and, after 48 h at 37°C, they were reweighed at 24- h intervals, until stabilization (final mass). The difference between the final and the initial mass determined the solvent capacity of each solvent. Data were subjected to analysis of variance and Tukey's test at 5% significance level. The results demonstrated that xylol was the most effective, especially on conventional gutta-percha and Resilon (p<0.05). Eucalyptol and orange oil were more effective on thermoplastic gutta-percha than the other materials (p<0.05). It was concluded that all evaluated substances presented solvent action, but xylol was the most effective on both gutta-percha or Resilon.
Keywords: Gutta-percha; Resilon; Retreatment; Solvent; cineole; cyclohexanol derivative; gutta percha; orange oil; resilon sealer; root canal filling material; solvent; terpene; vegetable oil; xylene; chemistry; Eucalyptus; human; materials testing; solubility; temperature; time; Cyclohexanols; Gutta-Percha; Humans; Materials Testing; Monoterpenes; Plant Oils; Root Canal Filling Materials; Solubility; Solvents; Temperature; Time Factors; Xylenes